Emergency contraception today: discussion of experts and practice - L V Erofeeva; V N Prilepskaya (IP Berlin A.V., 2014)
Emergency contraception with levonorgestrel for the practicing obstetricians-ginecologist is a well-known method of contraception. The modern science has analyzed the safety issues of its use, and recently has changed the understanding of the method mechanism of action, and also gave the answer to the particular question about the relationship of the patient` weight with the effectiveness of the levonorgestrel Emergency Contraception method.